Exophthalmos following mechanical thrombectomy for anterior circulation stroke: A retrospective study and review of literature. Issue 4 (August 2020) - Volders, D; Labrie, M; Keezer, M; Poppe, AY; Jacquin, G; Stapf, C; Gioia, L; Deschaintre, Y; Odier, C; Daneault, N; Iancu, D; Raymond, J; et al.
Background: Anecdotal cases of exophthalmos after acute mechanical thrombectomy have been described. We sought to estimate the incidence in a large cohort of patients with acute anterior circulation stroke treated with mechanical thrombectomy. Secondarily, we aimed to evaluate the underlying mechanism and to differentiate it on imaging from other pathology with similar clinical orbital features. Methods: Between November 2016 and November 2018, we performed a retrospective single-center study of 250 patients who underwent anterior circulation mechanical thrombectomy. Development of exophthalmos was independently evaluated by two readers on preprocedure and 24-h postprocedure non-contrast cerebral CT. Results: In the mechanical thrombectomy cohort, six individuals (2.4%) developed interval ipsilateral exophthalmos at 24 h. Of these, at least two patients developed clinical symptoms. There was almost perfect agreement between assessments of the two readers (Cohen's kappa = 0.907 (95% confidence interval: 0.726, 1.000)). In two patients, there was delayed ophthalmic artery filling on digital subtraction angiography. None of the patients had features of a direct carotid-cavernous fistula. Conclusions: Exophthalmos is not uncommon after mechanical thrombectomy (2.4%). The underlying mechanism is difficult to confirm, but it is most likely due to orbital ischemia from hypoperfusion or distal emboli.